The Effect of Financial Performance on The Adjustment of Health Company Capital Structure - Bandawaty, Euis; Nugraha; Disman; Sari, Maya (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Adjustments to capital structure adjustments are an important part of business activities, because the capital structure is closely related to the company's activities in the future. Failure to adjust the capital structure has an impact on the company's debt which is increasing, then it has an impact on the company's bankruptcy. Various studies have examined the capital structure of companies in emerging market countries and developed countries. The research results show the same or not the same pattern of influence between previous studies. On that basis, this study focuses on examining the effect of financial performance on the speed of capital structure adjustment. The object of this study is the performance characteristics of health companies contained in financial performance reports, the approach used is quantitative with a causal-descriptive method. The results of this study show that growth opportunities, corporate taxes, and liquidity have an influence on capital structure. This means that the company's financial performance must be in good condition so that the capital structure can be achieved, this pattern also applies to companies and other countries based on various previous studies. This condition indicates that it is important for companies to be able to manage financial performance properly, so that the company's finances can be in a safe condition to run the business in the future. This situation also makes investors see positive signals from companies that are able to manage company finances well.